PENGARUH GOOD CORPORATE GOVERNANCE PADA MANAJEMEN LABA PERUSAHAAN PENGAKUISISI SEBELUM MERGER DAN AKUISISI - Loekita, Vicentius Kelvin Kristianto; Sukartha, I Made (E-Jurnal Akuntansi; Vol 14 No 2 (2016), 2016)
The purpose of this study was to determine whether there is a management company profit before merger and acquisition and to determine whether the GCG effect on Earnings Management. This research was conducted at the Indonesian Stock Exchange (BEI). Data obtained shaped Indonesia Capital Market Dictionary (ICMD) and other historical reports in BEI period 2005-2013. Purposive sampling method used in this study and obtain a sample of 30 companies. Data collection method used in this study was non-participant observation method. The analysis technique used is a simple linear regression analysis. and the test Test Independent Sample T-Test Results of this study prove that the acquirer's earnings management prior to mergers and acquisitions. This shows that there has been a prior profit management company mergers and acquisitions. Good Corporate Governance negative effect on Earnings Management. This means that the higher the GCG then action Profit Management will be lower.
Keywords: good corporate governance; manajemen laba